Do COX-2 inhibitors raise blood pressure more than nonselective NSAIDs and placebo? An updated meta-analysis - Chan, C.; Reid, Christopher; Aw, T.; Liew, D.; Haas, S.; Krum, H. (Lippincott Williams & Wilkins, 2009)
BACKGROUND: Both COX-2 selective inhibitors (coxibs) and nonselective (ns)-NSAIDs elevate blood pressure (BP) and this may contribute to excess cardiovascular (CV) events. A number of recent large-scale randomized clinical trials (RCTs) comparing coxibs (including newer agents, lumiracoxib and etoricoxib) to both ns-NSAIDs and placebo have been reported, permitting an update to earlier BP analyses of these agents. DATA SOURCES/SYNTHESIS: Our search yielded 51 RCTs involving coxibs published before April 2008 with a total of 130 541 participants in which BP data were available. The Der Simonian and Laird random effects method for dichotomous variables was used to produce risk ratios (RR) for development of hypertension. RESULTS: For coxibs versus placebo, there was a RR of 1.49 (1.18g€"1.88, P = 0.04) in the development of new hypertension. For coxibs versus ns-NSAIDs, the RR was 1.12 (0.93g€"1.35, P = 0.23). These results were mainly driven by rofecoxib, with a RR of 1.87 (1.63g€"2.14, P = 0.08) versus placebo, and etoricoxib, with a RR of 1.52 (1.39g€"1.66, P = 0.01) versus ns-NSAID. CONCLUSION: On the basis of this updated meta-analysis, coxibs appear to produce greater hypertension than either ns-NSAIDs or placebo. However, this response was heterogeneous, with markedly raised BP associated with rofecoxib and etoricoxib, whereas celecoxib, valdecoxib and lumiracoxib appeared to have little BP effect. The relationship of this increased risk of hypertension to subsequent adverse CV outcomes requires further investigation and prospective RCTs. © 2009 Wolters Kluwer Health | Lippincott Williams & Wilkins.